A Review of Autism Spectrum Disorder Diagnostic Tools - Wan Azamudin, W. Z.; Syafeeza, A.R.; Ali, N. A.; Nor. N, Kamal (International Journal of Integrated Engineering, 2022)
This is an overview of diagnostic tools used in Malaysia. In this analysis, the benefits and disadvantages of each autism spectrum disorder diagnosis diagnostic technique are discussed. Pediatrists and psychiatric professionals who are focused on linguistic delay, brain function, or behavioural problems such as aggression, tantrum, etc. have currently noted the extent of impairments. The defects are assessed using multiple diagnostic tools. This review contrasts the seven forms of testing devices, including the Autism Diagnostic Observation Schedule (ADOS), Autism Diagnostic Interview-Revised (ADI-R), Childhood Autism Rating Scale (CARS), Gillian Autism Rating Scale (GARS), Diagnostic Interview for Social and Communication Disorder (DISCO), Developmental, Dimensional & Diagnostic Interview (3DI), and Diagnostic and Statistical Manual of Mental Disorder (DSM). The advantages and limitations of each tool are discussed in detail.